Effect of intradermal acupuncture combined with auricular acupoint pressing in the treatment of recurrent oral ulcers (皮内针联合耳穴压豆治疗复发性口腔溃疡的效果观察) - ZHU Yuhua (朱玉华); ZHU Feng (朱凤); LI Doudou (李逗逗); SUN Guifeng (孙贵凤) (中西医结合护理)
Objective To observe the effect of intradermal acupuncture acupuncture combined with auricular acupoint pressing therapy in the treatment of recurrent oral ulcers. Methods Totally 48 patients with recurrent oral ulcers were randomly divided into control group (n=24) and observation group (n=24). Patients in the control group were treated with watermelon frost cream spray, and patients in the observation group were treated with intradermal acupuncture acupuncture combined with auricular acupoint pressure. They were followed up for 6 months, and recovery from oral ulcers, reoccurrence of oral ulcers and adverse reactions were observed. Results After treatment, the total effective rate of the observation group was significantly higher than that of the control group (100. 00% vs. 83. 33%, P<0. 01). The time to burning pain relief and ulcer healing in the observation group were shorter than those of the control group(P<0. 01). There were 2 cases of recurrence reported in the observation group and 8 cases of reoccurrence reported in the control group(P＜0. 05). Adverse reaction was not observed in either of the two groups. Conclusion Intradermal acupuncture combined with auricular acupoint pressing therapy is potentially effective to shorten the time to pain relief and reduce the recurrence rate in patients with recurrent oral ulcers. It is an easy-to-operate technique with high patient acceptance. (目的 探讨皮内针联合耳穴压豆治疗复发性口腔溃疡的临床疗效。方法 48例复发性口腔溃疡患者随机分为对照组与观察组, 各24例。对照组采用西瓜霜喷剂治疗, 观察组在对照组基础之上给予皮内针联合耳穴压豆治疗。观察2组干预7 d后口腔溃疡恢复情况, 记录2组6个月内复发以及不良反应发生情况。结果 观察组复发性口腔溃疡治疗总有效率高于对照组, 差异有统计学意义(P＜0. 05)。观察组口腔局部灼痛缓解消失的时间、溃疡愈合的时间均短于对照组, 差异有统计学意义(P＜0. 05)。观察组复发2(8. 33%)例, 对照组复发8(33. 33%)例, 2组比较差异有统计学意义(P＜0. 05)。2组均未发生不良反应。结论 皮内针联合耳穴压豆治疗复发性口腔溃疡效果显著, 能有效缓解疼痛、减少复发, 且操作简单, 患者接受度高。)